The development of a Family Intervention Competency Assessment and Reflection Scale (FICARS) for psychosis. Issue 8 (20th November 2012) - Gamble, C.; Sin, J.; Kelly, M.; O'Loughlin, D.; Moone, N.
<x xml:space="preserve">Abstract</x> Accessible summary Family intervention (FI) has a robust evidence base yet no definitive instrument exists to outline what competences are required during and post FI training. A systematic approach commonly used in health outcomes measurement development identified and ratified components for a Family Intervention Competency Assessment and Reflection Scale (FICARS). FICARS implementation outcomes support the increasing emphasis on continuous learning and reflective practice integral to mental health practitioners' professional practice. Abstract Family intervention (FI) for psychosis has a robust evidence base. In recommending its use the revised NICE schizophrenia guideline states 'Healthcare professionals providing psychological interventions should have an appropriate level of competence'. Yet, no definitive instrument exists to outline what competences are required during and post FI training or help recruit staff with the appropriate knowledge and skill. This paper reports on the development of a Family Intervention Competency Assessment and Reflection Scale (FICARS). Using a systematic three‐staged approach commonly used in health outcomes measurement development, a comprehensive literature review on UK‐based FI training and commonly used assessment tools was undertaken. A FICARS draft was then constructed and revised in consultation with expert FI clinicians. Finally, a content validity study with FI trainers and students across three FI training programmes was undertaken to optimize FICARS aim to promote reflective assessment and professional development in FI skills and practice.